Evaluation of adipose derived stem cell therapy in a canine model of multiple sclerosis - Ahmed Nour Eldine Abdallah; Ashraf Aly Eldesoky Shamaa; Momtaz Abdelhady Shahin; Omar Mohammed Salah Eldin Eltookhy (Cairo : Ahmed Nour Eldine Abdallah, 2018)
Multiple sclerosis (MS) is a chronic, inflammatory, demyelinating disease of the central nervous system, whose etiology remains unknown. MS destroys oligodendrocytes, which are the cells responsible for creating and maintaining the myelin sheath, which helps the neurons carry electrical signals. This work aimed to evaluate the treatment of experimentally induced MS in dogs using laser activated adipose derived stem cells. Twenty-four animals were used in study divided into 2 main groups. All animals received bilateral intraspinal injection of 20 æl of 0.1 % Ethidium bromide in the lateral columns using a microneedle syringe attached to a capillary tube through a drilled hole at the first lumbar vertebra. Treatment using prepared Stem cell preparation was applied by injection of (10 X106 nucleated cells) directly in the CSF at the day 14 from the induction of the MS. Results showed amelioration of the clinical signs over time confirmed by the resolution of the previous lesions on MRI. Histopathology showed that injecting stem cells directly into the CSF lead to positive migration of the cells and homing into the site of the lesion as confirmed by PKH26 stain. Therapy lead to marked inhibition of apoptic activity, decreasing inflammation and glial scar formation, regeneration of the destructed axons, remyelination of the lost myelin as detected by increasing of Myelin Basic Proteins and differentiated into oligodendrocyte progenitors expressing Olig2 marker. The electron microscopy showed the remyelination sequence till forming a dense myelin sheath around the axons. From the forementioned results we concluded that treatment using laser activated stem cells holds a promising therapeutic option for treatment of MS
Thesis (Ph.D.) - Cairo University -Faculty of Veterinary Medicine - Department of Surgery -Anesthesiology and Radiology
Issued also as CD
Keywords: Demyelination; Multiple sclerosis; Spinal cord